2015
DOI: 10.1001/jamaophthalmol.2015.0325
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Adverse Effects of Phenylephrine Eyedrops

Abstract: IMPORTANCE Topical phenylephrine hydrochloride is routinely administered with few safety precautions, but evidence regarding its systemic safety to date is controversial. As even short-term variations in 24-hour blood pressure (BP) and heart rate (HR) can adversely affect cardiovascular health, better evidence on phenylephrine's effects on HR and BP is required.OBJECTIVE To perform a meta-analysis of available evidence regarding cardiovascular adverse effects of topical phenylephrine.DATA SOURCES PubMed, MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 17 publications
1
36
0
2
Order By: Relevance
“…Absorption of topical ocular drugs into the general circulation is associated with diverse AEs that are occasionally serious [8,23,24], and PE is not exempted [25,26]. PE is similar to epinephrine/norepinephrine in chemical structure and also has cardiovascular activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorption of topical ocular drugs into the general circulation is associated with diverse AEs that are occasionally serious [8,23,24], and PE is not exempted [25,26]. PE is similar to epinephrine/norepinephrine in chemical structure and also has cardiovascular activity.…”
Section: Discussionmentioning
confidence: 99%
“…Unintended systemic absorption of ocular PE can change blood pressure and heart rate. A systematic review of relevant randomized controlled trials indicated that these changes are only associated with PE-10% eyedrops, which transiently increase systolic blood pressure by 15 mmHg, and not the 2.5% concentration [26]. Although, these changes typically resolve within 60 min, even small alterations in blood pressure may have a negative impact on populations with predisposing comorbidities [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, an increased absorption even with these drugs could occur with a conjunctival hyperemia or epithelial damage to the cornea. Patients with hypertension, aneurysms, tachycardia, or cardiac disease must be treated with adequate caution 46. The use of phenylephrine 10% solution is not recommended (forbidden) for children and the elderly because of the increased risks of systemic toxicity 47,48…”
Section: Drug Classesmentioning
confidence: 99%
“…[12][13][14][15][16][18][19][20][21] It would probably be reasonable to assume wider applicability for a variety of medications but currently this is unproven and would require further studies. Other ophthalmic medications, for example F I G U R E 3 Boxplot showing differences in heart rate, blood pressure, IOP, and timolol plasma levels between groups T A B L E 1 levobunolol, brimonidine, atropine, cyclopentolate, scopolamine, phenylephrine and betamethasone are also absorbed in humans after topical ocular application.…”
Section: Discussionmentioning
confidence: 99%